Avantgarde Reliability Implications in Civil Engineering - Hassan, Maguid (IntechOpen, 2023)
Recent advances in relevant technologies have led to innovative solutions that can achieve reliable, resilient, and sustainable designs. Such characteristics are now considered essential for any newly designed engineering system. Such innovative solutions include applications of artificial intelligence in the design of integrated smart systems. This book discusses the implications of new concepts such as sustainability, resilience, health monitoring, and artificial intelligence on the reliability of designed systems.